Comparison of enhancement of anaerobic digestion of waste activated sludge through adding nano-zero valent iron and zero valent iron. Issue 48 (31st July 2018) - Wang, Yayi; Wang, Duanli; Fang, Huiying
Abstract : The feasibility of adding nano-zero valent iron to enhance anaerobic digestion of waste activated sludge was studied by comparison with ZVI, and the mechanisms of NZVI enhancement of the hydrolysis and methanogenesis processes were elucidated. Abstract : The feasibility of adding nano-zero valent iron (NZVI: 0.6, 1.0, 4.0, 10.0 g L −1 ) to enhance anaerobic digestion of waste activated sludge (WAS) was examined by comparison with ZVI, and the mechanisms of NZVI enhancement of the hydrolysis and methanogenesis processes were elucidated. NZVI could enhance hydrolysis–acidification of WAS by destroying the integrity of microbial cells. Both volatile fatty acids production and the acetic acid portion were greatly improved by NZVI additions, peaking at 4.0 g L −1 NZVI. In anaerobic digestion, CH4 production was promoted at a NZVI dosage ≤1.0 g L −1 . The optimum dosage of NZVI for methanogenesis was 1.0 g L −1, and further addition of NZVI could cause inhibition of methanogenesis because of long-term accumulation of H2 . ZVI could also improve hydrolysis–acidification and the CH4 yield, but its efficiency was relatively low compared with NZVI, and it could not induce cell wall rupture. 16S rDNA high-throughput sequencing results showed that NZVI addition at appropriate dosage facilitated increasing the proportion of microorganisms involved in WAS hydrolysis–acidification and methanogenesis.